Treatmenf of optic neuritis by retrobulbar injection of triamcinolone. - Gould, E S (1977)
In a single-blind controlled clinical trial patients with optic neuritis caused by demyelination were given a single retrobulbar injection of triamcinolone. Though the treated group showed a trend towards more rapid recovery of vision than the controls, there was no significant difference in visual acuity, colour vision, or visual fields during the first six months after treatment. We conclude that routine use of corticosteroids is not justified in unilateral optic neuritis when vision in the other eye is good. Shortening the period of visual disability in bilateral disease or unilateral disease when vision in the other eye is poor, however, may be justifiable.